1999
DOI: 10.1128/aac.43.11.2736
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Dissemination of Quinolone-Resistant Escherichia coli in the Community

Abstract: We studied the evolution of resistance to quinolones inEscherichia coli from 1992 to 1997 in Barcelona, Spain. An increasing proportion of quinolone-resistant E. coli (QREC) infections was observed. QREC strains were more common in patients with nosocomial infections but also increased in patients with community-acquired infections (9% in 1992 to 17% in 1996). Seventy (12%) of 572 episodes of E. coli bacteremia were due to QREC. Factors significantly associated with QREC bacteremia were the presence of underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
4
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(117 citation statements)
references
References 20 publications
6
99
4
8
Order By: Relevance
“…Most of the nalidixic acidresistant strains (31 of 36) came from poultry. These results correlate with the studies by Garau et al [34] who evaluated the prevalence of ciprofloxacin-resistant E. coli in the area of Barcelona (Spain) and found that 90.4% of the strains isolated from poultry were resistant to ciprofloxacin. Some studies have reported that the fluoroquinolone-resistant strains from poultry represent serologically and genetically diverse populations of various subgroups.…”
Section: Mechanisms Of Resistance To Quinolones In Escherichia Colisupporting
confidence: 92%
“…Most of the nalidixic acidresistant strains (31 of 36) came from poultry. These results correlate with the studies by Garau et al [34] who evaluated the prevalence of ciprofloxacin-resistant E. coli in the area of Barcelona (Spain) and found that 90.4% of the strains isolated from poultry were resistant to ciprofloxacin. Some studies have reported that the fluoroquinolone-resistant strains from poultry represent serologically and genetically diverse populations of various subgroups.…”
Section: Mechanisms Of Resistance To Quinolones In Escherichia Colisupporting
confidence: 92%
“…In 1999, Garau et al [21] described the dissemination of QREc in the community. They found significantly high prevalence rates of QREc in healthy-human fecal samples and in animal fecal samples of the same region.…”
Section: Discussionmentioning
confidence: 99%
“…In the decades following the introduction of FQs, quinolone resistance in Enterobacteriaceae has become common, widespread, and generally nonclonal. In this respect, it may be concluded that FQ resistance has emerged independently on many occasions [3][4][5].…”
Section: Introductionmentioning
confidence: 96%